PENGARUH CAPITAL EXPENDITURE, LEVERAGE, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Rosdiana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to investigate the effects of capital expenditure, leverage, managerial ownership, institutional ownership, and corporate social responsibility on firm value. We use Tobin’s Q as the proxy of firm value. Our sample firms are 11 mining firms listed in the Indonesian Stock Exchange for years 2018-2021. We generate our date from the official website of the Indonesian Stock Exchange. We run the multiple linear regression to analyze our data statistically. The results show that all independent variables simultaneously affect corporate value. Individual results indicate that managerial ownership (leverage) positively (negatively) affects firm value. However, other independent variables (institutional ownership and CSR) exhibit no significant influence on firm value.